Reconstructing Taxpayer Data Protection Through a Cyber-Restorative State Accountability Framework - Imam Cahyo Pornomo; Ismiyanto Ismiyanto; Hafid Zakariya (Jurnal Ilmu Hukum Kyadiren, 2026)
The digital transformation of tax administration has significantly improved the efficiency of public services; however, it has also heightened the risk of taxpayer data breaches involving highly sensitive personal and financial information. This study aims to examine the legal status of taxpayer data, identify the fragmentation of the regulatory framework governing taxpayer data protection, analyze state responsibility from a cyber law perspective, and develop a cyber-restorative state accountability framework. The research employs a normative legal methodology using statutory, conceptual, and comparative approaches. Data are analyzed prescriptively through systematic legal interpretation. The findings indicate that taxpayer data simultaneously constitute specific personal data, confidential tax information, and electronic information, each protected under multiple legal regimes. Nevertheless, the existing regulatory framework remains fragmented, resulting in inconsistencies in legal protection and state accountability. To address these shortcomings, this study proposes a cyber-restorative state accountability framework that integrates preventive measures, cybersecurity governance, breach notification, incident investigation, data recovery, and compensation mechanisms. The study concludes that reconstructing the legal framework based on this model is essential for strengthening legal certainty, enhancing state accountability, and fostering public trust in digital tax administration.